Exosomes secreted by cardiosphere-derived cells reduce scarring, attenuate adverse remodelling, and improve function in acute and chronic porcine myocardial infarction. (27th September 2016) - Gallet, Romain; Dawkins, James; Valle, Jackelyn; Simsolo, Eli; de Couto, Geoffrey; Middleton, Ryan; Tseliou, Eleni; Luthringer, Daniel; Kreke, Michelle; Smith, Rachel R.; Marbán, Linda; Ghaleh, Bijan; et al.
Translational perspective: Exosomes secreted by cardiosphere-derived cells (CDCs) were studied as a therapy for myocardial infarction (MI). In two different porcine models, exosomes from CDCs limited injury when given acutely and halted adverse remodelling when given in convalescent MI. Both models showed decreased scarring and improved function with intramyocardial delivery of exosomes. Cardiosphere-derived cell-secreted exosomes are a promising cell-free therapy for MI. Abstract : Aims: Naturally secreted nanovesicles known as exosomes are required for the regenerative effects of cardiosphere-derived cells (CDCs), and exosomes mimic the benefits of CDCs in rodents. Nevertheless, exosomes have not been studied in a translationally realistic large-animal model. We sought to optimize delivery and assess the efficacy of CDC-secreted exosomes in pig models of acute (AMI) and convalescent myocardial infarction (CMI). Methods and results: In AMI, pigs received human CDC exosomes (or vehicle) by intracoronary (IC) or open-chest intramyocardial (IM) delivery 30 min after reperfusion. No-reflow area and infarct size (IS) were assessed histologically at 48 h. Intracoronary exosomes were ineffective, but IM exosomes decreased IS from 80 ± 5% to 61 ± 12% ( P = 0.001) and preserved left ventricular ejection fraction (LVEF). In a randomized placebo-controlled study of CMI, pigs 4 weeks post-myocardial infarction (MI) underwent percutaneous IM delivery of vehicle ( n = 6) or CDC exosomes ( n = 6). Magnetic resonance imaging (MRI) performed before and 1 month after treatment revealed that exosomes (but not vehicle) preserved LV volumes and LVEF (−0.1 ± 2.2% vs. −5.4 ± 3.6%, P = 0.01) while decreasing scar size. Histologically, exosomes decreased LV collagen content and cardiomyocyte hypertrophy while increasing vessel density. Conclusion: Cardiosphere-derived cell exosomes delivered IM decrease scarring, halt adverse remodelling and improve LVEF in porcine AMI and CMI. While conceptually attractive as cell-free therapeutic agents for myocardial infarction, exosomes have the disadvantage that IM delivery is necessary.